CORRECTIVE FEEDBACK AND REPAIR STRATEGIES IN MEANING-FOCUSED LANGUAGE CLASSROOM - -, SULISTYANI; -, suhartono (Universitas Nusantara PGRI Kediri, 2014)
Abstract:The practice of corrective feedback in communicative language classroom has become a debate among applied linguists. Some consider it obstructs students’ fluent speech and some assert it is vital to show students their linguistic gaps. This study aims to describe the practice of oral corrective feedback in meaning-focused instruction specifically to answer the questions 1) what is to correct, 2) how it is corrected, and 3) how repair is constructed. The data are in the forms of teacher’s and students’ utterances obtained through video recording during meaning-focused instruction in a secondary school. The result shows that in meaning-focused instruction, the ESL teacher mainly corrects semantic errors and among six types of corrective feedback (explicit correction, recast, clarification request, metalinguistic feedback, elicitation, and repetition), the teacher mostly uses elicitation and recast while the repair strategies that occur in this class takes the pattern of other initiation-self repair. So, it can be concluded that in a meaning-focused instruction the teacher does not relatively interrupt the students’ fluent speech and that the communicative activity is maintained. And with self-repair, students notice their linguistic gaps. Therefore corrective feedback is still worth practicing in meaning-focused language classrooms.